2019
DOI: 10.1016/j.ccell.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of CDK12/CDK13 in Triple-Negative Breast Cancer

Abstract: Highlights d SR-4835, a potent dual inhibitor of CDK12/CDK13, provokes TNBC cell death d CDK12/CDK13 inhibition/loss promotes cleavage at intronic polyadenylation sites d CDK12 inhibition causes a BRCAness phenotype by blocking homologous recombination d SR-4835 acts in synergy with DNA-damaging chemotherapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
200
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(228 citation statements)
references
References 51 publications
5
200
1
1
Order By: Relevance
“…PL as a natural product extracted from pepper, which inhibits the expression levels of CDK1 and CDK4/6 and induces G2/M phase cell-cycle arrest to inhibit tumorigenesis [151]. Quereda et al found that SR-4835 is a highly selective dual inhibitor of CDK12 and CDK13, which can inhibit TNBC cell proliferation [80]. Panduratin A (PA) plays multiple roles with anti-inflammatory, antibacterial, antioxidant, and anti-cancer activity.…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…PL as a natural product extracted from pepper, which inhibits the expression levels of CDK1 and CDK4/6 and induces G2/M phase cell-cycle arrest to inhibit tumorigenesis [151]. Quereda et al found that SR-4835 is a highly selective dual inhibitor of CDK12 and CDK13, which can inhibit TNBC cell proliferation [80]. Panduratin A (PA) plays multiple roles with anti-inflammatory, antibacterial, antioxidant, and anti-cancer activity.…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Tumor suppressor Loss of CDK12 leads to downregulation of DDR 9 genes [61,76] Ovarian cancer (HGSOC 3 ) Tumor suppressor Loss of CDK12 leads to downregulation of DDR 9 genes [21,63,65] Prostate cancer (mCRPC 4 ) Tumor suppressor Loss of CDK12 leads to downregulation of DDR 9 genes [68,69] Gastric cancer Tumor promoter Overexpression of CDK12 actives the CDK12/CCL21 10 pathway [75]…”
Section: Cancer Type Cdk12 S Function Mechanism Referencesmentioning
confidence: 99%
“…Studies have indicated that THZ531 inhibits cell proliferation via preferentially suppressing the expression of DNA repair-related genes and inducing strong DDR in cancer cells [56]. Another novel CDK12/13 inhibitor, SR-4835, has been developed by Quereda's group [76]. It has potential for treatment of TNBC through the downregulation of core DDR genes and upregulation of genes involved in cell apoptosis.…”
Section: Cdk12 As a Potential Target And Biomarker For Cancer Therapymentioning
confidence: 99%
“…Cyclin-dependent kinase 12 (CDK12), a member of CDK family, was up-regulated and actively involved in the regulation of chemoresistance in BC. 18 A recent study claimed that CDK12 induced trastuzumab resistance by regulating WNT and IRS1-ErbB-PI3K signaling pathways in BC. 19 Besides, CDK12 down-regulation inhibited de novo and PARP inhibitor resistance in triple-negative BC.…”
Section: Introductionmentioning
confidence: 99%